Correlation between autochthonous microbial communities and key odorants during the fermentation of red pepper (Capsicum annuum L.). (October 2020) - Xu, Xinxing; Wu, Bingbing; Zhao, Wenting; Pang, Xueli; Lao, Fei; Liao, Xiaojun; Wu, Jihong
Abstract: High-throughput sequencing and gas chromatography-mass spectrometry (GC-MS) were used to investigate changes in bacterial and fungal communities and volatile flavor compounds during a 32-day fermentation process of red pepper ( Capsicum annuum L.). Key odorants were identified by olfactometry combined with GC-MS. Sixteen volatile compounds differed significantly after fermentation, including seven odorants. After fermentation, 1-butanol, 3-methyl-, acetate, phenol, 4-ethyl-2-methoxy-, octanoic acid, ethyl ester, styrene and 2-methoxy-4-vinylphenol were the key odorants, producing a flavor described as peppery, fruity, sour, and spicy. The correlation between microorganisms and odorants in the fermentation was studied and 18 odorants significantly correlated with the core microbial communities in the fermented samples. For further analysis, strains of seven genera were isolated and correlation analysis by O2PLS indicated that Aspergillus, Bacillus, Brachybacterium, Microbacterium and Staphylococcus were highly correlated with the flavor formation. These findings would help to understand the fermentation mechanism of fermented red pepper flavor formation. Graphical abstract: Image 1 Highlights: Shifts of microbial diversity were identified during fermentation. Different flavor metabolites before and after fermentation were ascertained. Aroma-producing core microorganism were analyzed. Key odorants and isolated strains were correlated.